Customers’ behavior changes of Russian representatives of generations X and Z due to social and economic factors in 2022 - L. G. Akhmaeva; D. V. Dolgopolov; A. I. Eremeeva (Вестник университета)
The article is devoted to the study of consumer expectations influence on the volume of produced spending within the framework of consumer preferences. The relevance of the study is related to the current processes in consumer market, which are characterized, on the one hand, by decrease in population income real volume, and on the other hand, by withdrawal of major international brands from Russia due to sanctions pressure. The classical theory of William Strauss and Neil Howe developed in 1991 was chosen as a methodological basis for demographic division of respondents of different generations. The purpose of the study is to analyze consumer preferences within two demographic generations (generations X and Z) related to spending due to expectation of crisis phenomena in consumer market. To test this hypothesis, a questionnaire survey was conducted among the representatives of the two generations. The respondents were students aged 17–21 (generation Z) and their parents aged 45–55 (generation X).